In Silico Studies on Bidara (Ziziphus mauritiana) Leaves Ethanol Extract Bioactive Ligands compared to Acarbose toward ?-glucosidase Enzyme - Merlita Herbani; yoni Rina Bintari (JIMR - Journal of Islamic Medicine Research, 2017)
ABSTRACTIntroduction : Diabetes mellitus has been widely concerned in human health. Diabetes mellitus has a huge amount of sufferers. Carbohydrate diet, which is needed for energy supply, contributes to uncontrolled postprandial blood glucose which worsens diabetes mellitus. ?-glucosidase is an enzyme that had been targeted to modify oligosaccharides, to decrease postprandial blood glucose. This study aims to predict the ability of the active compound contained in Z. mauritiana leaves to inhibit ?-glucosidase protein through an in silico study.Methods : Identified local Z. mauritiana leaves simplicial were extracted with 96% p.a ethanol solvent. The extract then analyzed with LCMS to confirm 6 active compound in the extract. Confirmed active compounds then undergo docking procedure, by downloading active compounds and acarbose molecular structure via PubChem, then converted to be 3D structure in pdb format by Pymol. Protein target ?-glucosidase molecular structure were obtained from Uniprot, and 3D structure built by Swissmodel. Docking process held by Pyrex by AutoDock Vina. Protein interaction ligands were visualized by Biovia Discovery Studio.Results : LCMS analysis revealed that there are apigenin, quercetin, routine, kaempferol, isovitexin and quercetin-3-rhamnoside in the extract. Molecular docking analysis explained that rutin has higher binding affinity than acarbose as the control. Rutin shared the same hydrogen bonding with acarbose in Arg 275 and Val 544.Conclusion : In conclusion, Z. mauritiana have potential as ?-glucosidase inhibitor.KEYWORDS : Ziziphus mauritiana ethanol extract Active Compound, Acarbose, in silico, ?-glucosidase